The "Ten Questions" of Eliezer Eilburg - Davis, Joseph M. 1960- (2011)
The Ten Questions of Eliezer Eilburg is one of the most radical works of Jewish philosophy of the sixteenth century. Written during the 1560s or 1570s, and addressed to three rabbis of Moravia, it challenges fundamental Jewish beliefs, such as Creation ex nihilo, the veracity and wisdom of the Torah, and individual reward and punishment. The work is among the first to question the reliability of the Masoretic text of the Bible. Eilburg draws on the medieval philosophical traditions of radical Maimonideanism and Jewish Averroism, but adds a new set of questions based on the historicist concerns of sixteenth-century Jewish intellectuals such as Azariah de' Rossi. The author was a German Jew, from a banking family of Braunschweig. After the expulsion of the Jews from that city in 1546, he studied philosophy and medicine in Ancona about 1551, and later lived in various places in Italy and Central Europe. Never before published, the work is edited here from the unique manuscript in the Library of the Jewish Theological Seminary of America. In addition to the Hebrew text, the edition includes Hebrew notes and section headings, and an English introduction.